(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
This article deals with case law precedents in which the courts have had to face sentences of legal incapacity dictated throughout the validity of the Civil Code, in order to adapt those judgments to the rules of the Civil and Commercial Code.